2014
DOI: 10.1007/s00167-014-3436-0
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intraobserver reliability of the Rockwood classification in acute acromioclavicular joint dislocations

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 17 publications
(19 reference statements)
0
42
0
1
Order By: Relevance
“…All clinical tests were negative in 12 patients, seven had one positive test, three had two positive tests, and one had three positive tests. The mean CS result at the follow-up was 93.44 ± 4.90 (range, 84-100), and the mean SST result was 10.78 ± 1.51 (range, [6][7][8][9][10][11][12]. There was no statistically significant association between the CS results and either shoulder tests or radiological findings.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…All clinical tests were negative in 12 patients, seven had one positive test, three had two positive tests, and one had three positive tests. The mean CS result at the follow-up was 93.44 ± 4.90 (range, 84-100), and the mean SST result was 10.78 ± 1.51 (range, [6][7][8][9][10][11][12]. There was no statistically significant association between the CS results and either shoulder tests or radiological findings.…”
Section: Resultsmentioning
confidence: 92%
“…Considering that Tossy III consists of Rockwood III-VI and the majority of our patients are young and active, in clinical work we prefer the Tossy classification. It would probably be more beneficial to use the Rockwood classification in clinical work because recent literature defines the Rockwood classification as a gold standard for grading ACJ dislocations, and shows excellent inter-and intra-observer reliability for acute ACJ dislocations [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las luxaciones tipo iv pueden presentar menor deformidad, ya que el desplazamiento es en dirección posterior. Para diferenciar una luxación tipo iii de una tipo v hay que valorar si esta es reductible o no 11 . Para ello, se estabiliza la escápula con una mano y se realiza un movimiento en dirección proximal desde el codo ipsilateral, pudiendo reducirse tan solo en las tipo iii.…”
Section: Deformidadunclassified
“…2 Although this is still the commonly used classification system, recent studies have suggested an overall lack of reliability of the Rockwood classification of ACJ dislocations and of decisions regarding their treatment. 3,4 Less severe (types I, II and III) ACJ injuries are more common, 2 with recent studies suggesting that of those who present to hospital, the most common are type III injuries. 5 The treatment of ACJ injuries can be broadly stratified by the severity of the injury, with type I and II injuries almost universally treated conservatively with expected return to painless full range of motion few weeks after the injury.…”
Section: Introductionmentioning
confidence: 99%